2015
DOI: 10.3389/fpsyg.2015.01760
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Functioning, Self-Esteem, and Psychological Distress in Adults Whose Parents are Separated/Divorced

Abstract: Objective: The objective of this research was to identify retrospectively the alienating behaviors and the parental bonding that occurred in an Italian sample of adults whose had parents separated or divorced and their associations with self-esteem and psychological distress.Methods: Four hundred seventy adults in Chieti, Italy, completed an anonymous and confidential survey regarding their childhood exposure to parental alienating behaviors (using the Baker Strategy Questionnaire), quality of the parent–child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…Our results are consistent with prior studies reporting high correlations among experiences of hostility, rejection, humiliation and parental criticism and the development of a representation of the self that is characterized by feelings of low self-worth, shame, guilt, and propensity to adopt a punitive self-stance, as a consequence of an internalization of a highly critical family environment ( Soffer et al, 2008 ; Kopala-Sibley and Zuroff, 2014 ; Baetens et al, 2015 ; Verrocchio et al, 2015 ). In a recent meta-analysis, Liu et al (2017) found that emotional abuse had the strongest effect on suicidal behavior compared to other types of maltreatment.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with prior studies reporting high correlations among experiences of hostility, rejection, humiliation and parental criticism and the development of a representation of the self that is characterized by feelings of low self-worth, shame, guilt, and propensity to adopt a punitive self-stance, as a consequence of an internalization of a highly critical family environment ( Soffer et al, 2008 ; Kopala-Sibley and Zuroff, 2014 ; Baetens et al, 2015 ; Verrocchio et al, 2015 ). In a recent meta-analysis, Liu et al (2017) found that emotional abuse had the strongest effect on suicidal behavior compared to other types of maltreatment.…”
Section: Discussionsupporting
confidence: 92%
“…Understanding the co-occurrence and temporal dynamics of hyperactivity/inattention and emotional symptoms may be significant for explaining the development of hyperactivity/inattention from childhood through adolescence and into adulthood. In addition, a closer exploration of these processes is warranted because the additional presence of emotional symptoms can significantly affect quality of life, academic performance, adult adjustment, and lifetime psychiatric comorbidities ( Wehmeier et al, 2010 ; Seymour et al, 2012 ; Verrocchio et al, 2015 ). Our findings show that emotional symptoms of children significantly predicted their hyperactivity/inattention.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of quick recognition of this form of psychological maltreatment can be detrimental to the child’s mental health. In particular, research has widely confirmed the negative impact of PA on children, with outcomes ranging from psychopathology (e.g., depression, anxiety, substance abuse, and conduct disorders) to poor academic performance and low self-esteem (Baker, 2007; Ben-Ami & Baker, 2012; Saini et al, 2016; Verrocchio et al, 2016; Verrocchio et al, 2019; Verrocchio & Baker, 2015).…”
Section: Introductionmentioning
confidence: 99%